Integrating barcode technology into warehouse management systems for enhanced efficiency and inventory accuracy - Deepali, Charumati; Monika, Priyankan; Dharmendra, Sonali (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2024)
This research explores the integration of barcode technology into Warehouse Management Information Systems (WMS) to optimize warehouse operations. Through a comprehensive review of literature, case studies, and industry practices, the study investigates the benefits, challenges, and best practices associated with barcode-based WMS implementation. Key findings reveal the transformative impact of barcode technology on operational efficiency, inventory accuracy, and order processing speed in warehouses. A framework for designing barcode-based WMS is developed, providing practical guidance for organizations seeking to leverage technology to enhance warehouse management practices. The implications of the research extend to businesses, employees, customers, and supply chain partners, highlighting opportunities for cost savings, productivity improvement, and customer satisfaction.